2006
DOI: 10.1029/2006gl027768
|View full text |Cite
|
Sign up to set email alerts
|

Validating land cover maps with Degree Confluence Project information

Abstract: [1] We propose the use of Degree Confluence Project (hereby DCP) information as a new method for validating land cover maps. The DCP is a volunteer-based project that aims to collect onsite information from all the degree confluences (intersections of integer level latitude and longitude gridlines) in the world. We assessed the reliability and effectiveness of DCP-derived data in validating land cover maps. As a result, we obtained land cover validation information superior to the validation information obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 9 publications
3
69
0
1
Order By: Relevance
“…Strahler, 2006) but many land cover datasets are not validated using these protocols (Foody, 2002). The Geo-Wiki approach offers great potential to contribute to land cover validation (Iwao et al, 2006;Fritz et al, 2012). producer's accuracies.…”
Section: Background: Geo-wiki and Land Cover Accuracymentioning
confidence: 99%
“…Strahler, 2006) but many land cover datasets are not validated using these protocols (Foody, 2002). The Geo-Wiki approach offers great potential to contribute to land cover validation (Iwao et al, 2006;Fritz et al, 2012). producer's accuracies.…”
Section: Background: Geo-wiki and Land Cover Accuracymentioning
confidence: 99%
“…It has been shown that the photographs and description of the confluence points can be a valuable resource for land cover validation exercises and accuracy assessments. Recently an accuracy assessment based on the confluence project has been carried out for the GLC-2000 and MODIS maps and for two older global land cover products: the Global land cover of the University of Maryland (UMD) and the Global land cover characteristics database (GLCCD) [22].…”
Section: Visualizing Baseline Data Confluence Points and Panoramiomentioning
confidence: 99%
“…The use of the confluence points (www.confluence.org) for land cover validation [22] has demonstrated that pictures are a very valuable resource for validation activities related to land cover. We have therefore implemented the option for each validation which is undertaken for the three different land cover products to be complemented by pictures.…”
Section: Supporting Picture Validationmentioning
confidence: 99%
“…However, new approaches such as crowdsourcing (citizen observatories) have indicated that the collection of large collections of ground information is now feasible (Schuurman 2009;Heipke 2010;Goodchild 2007). Recent efforts have shown the potential to use citizen observed data to validate land cover maps (Iwao et al 2006;Fritz et al 2009). Similar efforts have the potential to provide the input to enhance our characterization of landscape structure information at larger scales.…”
Section: Ways Forwardmentioning
confidence: 99%